Wrist injuries in gymnasts: Systematic review - Đorđević Dušan; Stanković Mima; Ilić Predrag (College of Sports and Health, Belgrade, 2021)
The aim of this research was to summarize the relevant literature on wrist injuries in gymnasts and to determine the prevalence of injuries based on a systematic review of previous research. In sports gymnastics, the upper extremities are the bearers of the whole body, which leads to consequences such as wrist injuries. The types of injuries are different, depending on its excessive use. The combination of a period of rapid growth and intensive training creates the conditions for gymnasts to be more prone to injuries, especially wrist injuries. Electronic search of papers was performed in databases: KoBSON, PubMed and Google Academic, and the studies were published in the period from 2010 to 2020, while a descriptive method was used to analyse the obtained data. Based on the database search, 14 studies met the criteria. Subjects who participated in questionnaires and experiments and different types of corrective treatment, sought to prevent further progression of the injury, and most subjects made major progress in suppressing or completely regressing their wrist injury. Raising awareness of the existence of this injury is of great importance in sport gymnastics, so early detection and prevention of injury is crucial.